Ginn Library staff - Unknown (Tufts Archival Research Center, 2014)
From left to right in reverse chronological order that they worked in the Library: Daniel Hurwit, Lindsey Tapper, Linda Batista, Muriel Prentice, and Linda Warner. Taken at the retirement party for Karin McMaster, Fletcher Administrative Assistant.